Assessment of a bifendate derivative bearing a 6, 7-dihydro-dibenzo[c, e]azepine scaffold as a potential anti-metastatic agent. Issue 11 (25th September 2018) - Qiu, Jingying; Chen, Wang; Jiang, Yanfei; Chen, Jing; Zhang, Yinpeng; Gu, Xiaoke
Abstract : 4i exhibited significant anti-metastatic activity in MDA-MB-231 cells via inhibiting MMP-2/9 activity and expression. Abstract : Multidrug resistance (MDR) and metastasis are major causes of mortality in patients with cancer. We recently reported a bifendate derivative bearing a dibenzo[ c, e ]azepine scaffold (4i ) as a P-gp and BCRP-medicated MDR reversal agent. As a continuation of the previous research, its ability to inhibit cancer metastasis was investigated in MDA-MB-231 cells in the present work. Wound-healing and chamber migration assays showed that4i could significantly attenuate the migration of MDA-MB-231 cells. Additionally, 4i obviously suppressed the invasive activity of MDA-MB-231 cells, thus displaying potential anti-metastasis activity. Preliminary mechanism studies indicated that the anti-metastasis activity of4i was associated with the inhibitory effect on the activity and expression of MMP-2 and MMP-9. These results, together with the previous findings, suggest that compound4i could be a promising lead for the development of novel anti-cancer agents with anti-MDR and metastatic activities.